Functional Analysis of the NucS/EndoMS of the Hyperthermophilic Archaeon Sulfolobus islandicus REY15A - Ahmad, Sohail; Huang, Qihong; Ni, Jinfeng; Xiao, Yuanxi; Yang, Yunfeng; Shen, Yulong (Frontiers in Microbiology, 2020)
EndoMS is a recently identified mismatch specific endonuclease in Thermococcales of Archaea and Mycobacteria of Bacteria. The homologs of EndoMS are conserved in Archaea and Actinobacteria, where classic MutS-MutL-mediated DNA mismatch repair pathway is absent or non-functional. Here, we report a study on the in vitro mismatch cleavage activity and in vivo function of an EndoMS homolog (SisEndoMS) from Sulfolobus islandicus REY15A, the model archaeon belonging to Crenarchaeota. SisEndoMS is highly active on duplex DNA containing G/T, G/G, and T/T mismatches. Interestingly, the cleavage activity of SisEndoMS is stimulated by the heterotrimeric PCNAs, and when Mn2+ was used as the co-factor instead of Mg2+, SisEndoMS was also active on DNA substrates containing C/T or A/G mismatches, suggesting that the endonuclease activity can be regulated by ion co-factors and accessory proteins. We compared the spontaneous mutation rate of the wild type strain REY15A and ∆endoMS by counter selection against 5-fluoroorotic acid (5-FOA). The endoMS knockout mutant had much higher spontaneous mutation rate (5.06 × 10−3) than that of the wild type (4.6 × 10−6). A mutation accumulation analysis also showed that the deletion mutant had a higher mutation occurrence than the wild type, with transition mutation being the dominant, suggesting that SisEndoMS is responsible for mutation avoidance in this hyperthermophilic archaeon. Overexpression of the wild type SisEndoMS in S. islandicus resulted in retarded growth and abnormal cell morphology, similar to strains overexpressing Hje and Hjc, the Holliday junction endonucleases. Transcriptomic analysis revealed that SisEndoMS overexpression led to upregulation of distinct gene including the CRISPR-Cas IIIB system, methyltransferases, and glycosyltransferases, which are mainly localized to specific regions in the chromosome. Collectively, our results support that EndoMS proteins represent a noncanonical DNA repair pathway in Archaea. The mechanism of the mismatch repair pathway in Sulfolobus which have a single chromosome is discussed.